Oxidized LDL triggers changes in oxidative stress and inflammatory biomarkers in human macrophages (2018)
ABSTRACT: Oxidized low-density lipoprotein (oxLDL) is a well-recognized proatherogenic particle that functions in atherosclerosis. In this study, we established conditions to generate human oxLDL, characterized according to the grade of lipid and protein oxidation, particle size and oxylipin content. The induction effect of the cellular proatherogenic response was assessed in foam cells by using an oxLDL-macrophage interaction model. Uptake of oxLDL, reactive oxygen species production and expression of oxLDL receptors (CD36, SR-A and LOX-1) were significantly increased in THP-1 macrophages. Analyses of 35 oxylipins revealed that isoprostanes (IsoP) and prostaglandins (PGs) derived from the oxidation of arachidonic, dihomo gamma-linolenic and eicosapentaenoic acids were strongly and significantly induced in macrophages stimulated with oxLDL. Importantly, the main metabolites responsible for the THP1-macrophage response to oxLDL exposure were the oxidative stress markers 5-epi-5-F2t-IsoP, 15-E1t-IsoP, 8-F3t-IsoP and 15-keto-15-F2t-IsoP as well as inflammatory markers PGDM, 17-trans-PGF3α, and 11β-PGF2α, all of which are reported here, for the first time, to function in the interaction of oxLDL with THP-1 macrophages. By contrast, a salvage pathway mediated by anti-inflammatory PGs (PGE1 and 17-trans-PGF3α) was also identified, suggesting a response to oxLDL-induced injury. In conclusion, when THP-1 macrophages were treated with oxLDL, a specific induction of biomarkers related to oxidative stress and inflammation was triggered. This work contributes to our understanding of initial atherogenic events mediated by oxLDL-macrophage interactions and helps to generate new approaches for their modulation.